Slim electrodes for improved targeting in deep brain stimulation. (19th March 2020) - Villalobos, Joel; McDermott, Hugh J; McNeill, Peter; Golod, Aharon; Rathi, Vivek; Bauquier, Sébastien H; Fallon, James B
Abstract: Objective. The efficacy of deep brain stimulation can be limited by factors including poor selectivity of stimulation, targeting error, and complications related to implant reliability and stability. We aimed to improve surgical outcomes by evaluating electrode leads with smaller diameter electrode and microelectrodes incorporated which can be used for assisting targeting. Approach . Electrode arrays were constructed with two different diameters of 0.65 mm and the standard 1.3 mm. Micro-electrodes were incorporated into the slim electrode arrays for recording spiking neural activity. Arrays were bilaterally implanted into the medial geniculate body (MGB) in nine anaesthetised cats for 24–40 h using stereotactic techniques. Recordings of auditory evoked field potentials and multi-unit activity were obtained at 1 mm intervals along the electrode insertion track. Insertion trauma was evaluated histologically. Main results . Evoked auditory field potentials were recorded from ring and micro-electrodes in the vicinity of the medial geniculate body. Spiking activity was recorded from 81% of the microelectrodes approaching the MGB. Histological examination showed localized surgical trauma along the implant. The extent of haemorrhage surrounding the track was measured and found to be significantly reduced with the slim electrodes (541 ± 455 µ m vs. 827 ± 647 µ m; P < 0.001). Scoring of the trauma, focusing on tissue disruption, haemorrhage, oedema of glial parenchyma and pyknosis, revealed a significantly lower trauma score for the slim electrodes ( P < 0.0001). Significance . The slim electrodes reduced the extent of acute trauma, while still providing adequate electrode impedance for both stimulating and recording, and providing the option to target stimulate smaller volumes of tissue. The incorporation of microelectrodes into the electrode array may allow for a simplified, single-step surgical approach where confirmatory micro-targeting is done with the same lead used for permanent implantation.